Persistence of Parvovirus B19 (B19V) DNA and humoral immune response in B19V‐infected blood donors. Issue 3 (11th June 2014) - Juhl, D.; Görg, S.; Hennig, H.
<x xml:space="preserve">Abstract</x> Background and Objectives Parvovirus B19 (B19V) DNA seems to persist in the plasma of B19V‐infected blood donors. The relevance of this for recipients of single‐donor blood components is yet unclear. Material and Methods We studied serial archive and follow‐up samples from 75 B19V‐infected blood donors to obtain more data about the duration and degree of viraemia and the presence of IgG and IgM anti‐B19V. IgG antibodies were further characterized by Western blot analysis in 29 donors. Results In 411 B19V DNA‐positive samples collected, we found high concentrations (>106 IU B19V DNA/ml plasma) in five. B19V DNA persisted for a mean of 21·5 months (range: 2·3–52·4; 95% confidence interval, 19·1–23·9 months) in all donors. Only 15 such samples had either no or low‐titre IgG anti‐B19V. IgG antibodies were predominantly directed against epitopes on the minor capsid protein VP1, thus probably of neutralizing type with high avidity. IgM anti‐B19V was detectable in 9/13 samples with high DNA concentrations. Conclusions The vast majority of single‐donor blood components with detectable B19V DNA are probably not infectious for their recipients because DNA is at only low levels and the donors also have potentially neutralizing antibodies with high avidity. Anti‐B19V IgM testing does not identify every donation with high B19V DNA concentrations, but, in addition to B19V NAT testing, donors with persistent IgG anti‐B19V might be considered 'B19V‐safe' for single‐donor blood components.